Use of Computer-Assisted Instrument Guidance Technology by Student Registered Nurse Anesthetists for Simulated Invasive Procedures. - Hauglum, Shayne D. (AANA Journal, 2020)
This study was conducted to determine if computerassisted instrument guidance (CAIG, Clear Guide Medical), with an optical tracking mechanism, enhances simulated transversus abdominis plane (TAP) block performance in a porcine model by novice student registered nurse anesthetists (SRNAs) compared with standalone ultrasonography (US). In a crossover design, 26 students were randomly assigned into 2 groups: US only and CAIG. Performance was assessed using a task-specific checklist survey tool and a global rating scale to assess performance. Time to hydrodissection and number of insertion attempts were recorded. A pre-procedure and postprocedure survey obtained participants' demographics and measured overall experience. Results revealed higher mean scores for all items in the global rating scale and overall performance (P = .010). The checklist survey results indicated no signifi- cant between-group differences. The CAIG group was observed to have significantly lower simulated block performance times (P = .037) and number of attempts (P = .002). The postprocedure survey results showed most participants (88%) reported an enhanced experience using the CAIG. Use of the CAIG showed favorable results in novice SRNAs performing the simulated block. Procedure performance, number of attempts, and time to complete were significantly lower, with a strong preference for the CAIG system.